Big splash! The grunt and the grouch - Corderoy, Tracey; Wildish, Lee (North Mankato, Minnesota Stone Arch Books, 2012)
In this trio of adventures Grunty and Grouchy, a pair of trolls, always seem to find trouble whatever they are doing
1 2 13
Keywords: Humorous stories; Trolls -- Juvenile fiction; Trolls -- Fiction